Evolution of the methodological quality of controlled clinical trials for myofascial trigger point treatments for the period 1978–2015: A systematic review. (August 2017) - Stoop, Rahel; Clijsen, Ron; Leoni, Diego; Soldini, Emiliano; Castellini, Greta; Redaelli, Valentina; Barbero, Marco
Abstract: Background: The methodological quality of controlled clinical trials (CCTs) of physiotherapeutic treatment modalities for myofascial trigger points (MTrP) has not been investigated yet. Objectives: To detect the methodological quality of CCTs for physiotherapy treatments of MTrPs and demonstrating the possible increase over time. Design: Systematic review. Methods: A systematic search was conducted in two databases, Physiotherapy Evidence Database (PEDro) and Medicine Medical Literature Analysis and Retrieval System online (MEDLINE), using the same keywords and selection procedure corresponding to pre-defined inclusion criteria. The methodological quality, assessed by the 11-item PEDro scale, served as outcome measure. The CCTs had to compare at least two interventions, where one intervention had to lay within the scope of physiotherapy. Participants had to be diagnosed with myofascial pain syndrome or trigger points (active or latent). Results: A total of n = 230 studies was analysed. The cervico-thoracic region was the most frequently treated body part (n = 143). Electrophysical agent applications was the most frequent intervention. The average methodological quality reached 5.5 on the PEDro scale. A total of n = 6 studies scored the value of 9. The average PEDro score increased by 0.7 points per decade between 1978 and 2015. Conclusions: The average PEDro score of CCTs for MTrP treatments does not reach the cut-off of 6 proposed for moderate to high methodological quality. Nevertheless, a promising trend towards an increase of the average methodological quality of CCTs for MTrPs was recorded. More high-quality CCT studies with thorough research procedures are recommended to enhance methodological quality. Highlights: The CCT time distribution of all studies ranged from the years 1978–2015. The most frequently treated body part was the cervico-thoracic region with 62%. The most frequently used intervention was electrophysical agent application (43%). The average methodological quality reached 5.5/10 on the PEDro scale. An average increase in the PEDro score by 0.7 points each decade was revealed.